Kekerabatan Bahasa Sunda dan Bahasa Bali - Oktaviana, Ika; Junawaroh, Siti (Faculty of Humanities, Diponegoro University, 2024)
In the field of comparative historical linguistics, examining language kinship can illuminate the relationships between languages in a particular region and their evolutionary paths over time. Sundanese and Balinese are two prominent languages that originated in different areas of Indonesia, yet both are part of the Austronesian language family. This study aims to investigate the kinship relationship between Sundanese and Balinese by employing lexicostatistics and phonemic correspondence techniques, providing a structured approach to analyzing their linguistic connections. Data collection was conducted through interviews, focusing on 200 Swadesh vocabulary words that encompass basic terms. The findings reveal a kinship degree of 41% between Sundanese and Balinese, indicating that they diverged approximately 2,058 years ago. Several phonemic correspondences were identified, including /a ə/, /ɣ ə/, /d r/, and /a,u/ o/. The analysis further unveiled sound change processes such as lenition, merger, and splitting. Notably, Sundanese appears to be more closely aligned with Proto-Austronesian (PAN) than Balinese, as it has preserved certain phonemes, including /b/, /d/, and /h/, without significant alterations. These findings support the conclusion that Sundanese and Balinese belong to the same language family classification.